Rancang Bangun Robot Beroda Penggerak Kipas dengan Deteksi Api Berbasis Mikrokontroler Atmega328 - Roby Anggi Maresya Putra; Asruddin Asruddin; Yoga Listi Prambodo (Sistem Komputer & Teknologi Intelegensi Artifisial (SIKOMTIA), 2023)
Electricity is inseparable from human daily life. Many devices operate by utilizing electrical energy. If there is negligence in its usage, it can cause electrical short circuits and even lead to fires. Fires that occur can have a significant impact on the surrounding community and the environment. To address this issue, a prototype in the form of a robot needs to be developed, which has the ability to detect and extinguish fires. Utilizing technological advancements such as fire detection sensors that can communicate with a microcontroller to search for and detect the presence of fire, as well as assistance from ultrasonic sensors to detect obstacles. The fire extinguishing mechanism of this robot prototype utilizes a fan module that becomes active when a fire is detected.